Phenolic isomers from plantago catharinea leaves: Isolation, identification, quantification and in vitro antioxidant activity - De Souza Mesquita, Leonardo Mendes [UNESP]; Da Rocha, Claudia Quintino [UNESP]; Affonso, Luiz Henrique Lima [UNESP]; Cerulli, Antonietta; Piacente, Sonia; Tangerina, Marcelo Marucci Pereira [UNESP]; Martins, Maria Bernadete Gonçalves [UNESP]; Vilegas, Wagner [UNESP] (My University, 2017)
In this study we isolated two polyphenolic acids of m/z 639, called catharinol A and catharinol B, from Plantago catharinea L. (Plantaginaceae) leaves. Although presenting very similar structures, catharinol A showed higher antioxidant activity when compared with gallic acid and quercetin standards. These compounds are position isomers and present in their chemical structure the rare sugar D-allose. Molecules with similar constitution are known to have important biological activities such as antitumor and immunosuppressive. These compounds were isolated by high-performance liquid chromatography (HPLC) and characterized by mass spectrometry (FIA-ESI-IT-MS/MS) and nuclear magnetic resonance (NMR). This work is the first study on the chemical composition of P. catharinea and encourages the production of Plantago species as a good source of bioactive molecules.
Keywords: Antioxidant activity; D-allose; Plantago; Polyphenolic acids